ISLAMIC CORPORATE FINANCE - Hassan, Kabir, editor 243046; Rashid, Mamunur, editor 632571; Aliyu, Sirajo, editor (Abingdon, Oxon ; New York, NY : Routledge, 2019)
Most existing texts covering topics in Islamic finance discuss the potential of Islamic banking; very few talk about other forms of financing and the investment activities of Islamic firms from the standpoint of owners and managers. This book fills this gap by looking at the traditional as well as non-traditional financing andinvestment activities of shariah-compliant companies. The chapters in this edited text offer a full range of topics on corporate finance for Islamic firms, including global comparisons of shariah screening, dividend policy and capital structure of Islamic firms, details of global Islamic equity markets, trends and performance of sukuk markets, and a brief account of derivative securities that can be used in Islamic finance. This is a useful reference for anyone who wishes to learn more about the performance of shariah-compliant companies vis-a-vis conventional firms. The book includes both technical and non-technical information that would be suitable for classroom teaching as well as a reference for postgraduate research students.